2012
DOI: 10.1103/physrevlett.108.153605
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Source of Photon Pairs

Abstract: The creation of monolithically integratable sources of single and entangled photons is a top research priority with formidable challenges: The production, manipulation, and measurement of the photons should all occur in the same material platform, thereby fostering stability and scalability. Here we demonstrate efficient photon pair production in a semiconductor platform, gallium arsenide. Our results show type-I spontaneous parametric down-conversion of laser light from a 2.2 mm long Bragg-reflection waveguid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
141
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 28 publications
(34 reference statements)
6
141
0
Order By: Relevance
“…On the other hand, quantum logic ports and circuits for quantum computing algorithms have been demonstrated in integrated photonic chips [1,2]. It is foreseeable that on-chip sources of single and entangled photons at telecom wavelengths will represent a key enabling technology for quantum communication and computing [3], thus motivating an intense research activity [4][5][6][7][8][9][10]. Among the different approaches proposed so far, microcavities [11] are a very promising solution because of the field enhancement that they provide (for example the pair production rate for a χ (3) triply resonant cavity scales as the sixth power of the cavity enhancement factor [12]).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quantum logic ports and circuits for quantum computing algorithms have been demonstrated in integrated photonic chips [1,2]. It is foreseeable that on-chip sources of single and entangled photons at telecom wavelengths will represent a key enabling technology for quantum communication and computing [3], thus motivating an intense research activity [4][5][6][7][8][9][10]. Among the different approaches proposed so far, microcavities [11] are a very promising solution because of the field enhancement that they provide (for example the pair production rate for a χ (3) triply resonant cavity scales as the sixth power of the cavity enhancement factor [12]).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, photonic chips able to realize the logic ports required for quantum computing have been recently demonstrated [11,12]. On the other hand, an intense research activity has been dedicated to implement on chip sources of single and entangled photons [6,7,[13][14][15][16][17]. A detailed review on the genesis and evolution of integrated quantum optics can be found in [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this last case, the relevant property of the two photons is that they are generated exactly at the same time, and thus can be exploited for heralding the presence of one single photon on the idler beam upon detection of a photon in the signal beam. While SPDC is nowadays a common tool in many quantum optical labs for generating quantum states of light, it typically relies on bulky setups and large efforts have been dedicated in the past years for reducing the footprint of these systems [6][7][8]. Following a trend typical for classical optics, the first step has been the generation of quantum states in optical fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Also nonlinear waveguides, for which strong spatial localization of optical fields in the transverse plane is characteristic, profit from enhancement of the effective nonlinearity. This enhancement has been widely exploited when generating photon pairs in classical [15][16][17], multi- * Electronic address: perinaj@prfnw.upol.cz layer [18], Bragg-reflection [19,20] and photonic-wire [21] waveguides. Effective nonlinearity in a waveguide can also be increased by the use of mode coupling through evanescent waves with fields in a neighboring waveguide.…”
Section: Introductionmentioning
confidence: 99%